Program Studi Pendidikan Ekonomi: Pintu Gerbang Menuju Pemahaman Ekonomi Masa Kini: Pembentuk tenaga pendidik dibidang ekonomi yang kompeten - Bima Lubis (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This article discusses the economics education study program as an academic field that integrates economics with teaching methodology. The program aims to produce competent educators to teach economic concepts in schools and universities. The curriculum encompasses economic theory, teaching methodology, and practicums, with career prospects as teachers, lecturers, or consultants. Challenges include the theory-practice gap and the adoption of digital technology. The article emphasizes the program's role in supporting economic literacy and human resource development in Indonesia, while also providing insights into its history, university examples, and global trends.